A Leri-Weill dyschondrosteosis patient confirmed by mutation analysis of gene - Won Bok Choi; Seung Hyeon Seo; Woo Hyun Yoo; Su Young Kim; Min Jung Kwak (Korean Society of Pediatric Endocrinology, 2015)
Leri-Weill dyschondrosteosis is characterized by SHOX deficiency, Madelung deformity, and mesomelic short stature. In addition, SHOX deficiency is associated with idiopathic short stature, Turner syndrome, and Langer mesomelic dysplasia. We report the first case of a Leri-Weill dyschondrosteosis patient confirmed by SHOX gene mutation analysis in Korea. The patient, who was a 7-year-old female, showed short stature. Her height and weight were 108.9 cm (<3rd percentile) and 19.7 kg (5th-10th percentile), respectively. Her arm span, height of trunk, leg length, and sitting length were 100.5 cm, 58 cm, 50.9 cm, and 62.5 cm, respectively. Her body proportion was 1.13:1. Extremities to trunk ratio was 2.61. Her hand radiograph showed Madelung deformity. And the growth hormone stimulation test showed a normal response. Furthermore, because of Madelung deformity with idiopathic short stature, she was suspected of SHOX deficiency. We performed SHOX gene mutation analysis and found a c.491G>A (p.W164X) mutation of the SHOX gene. Accordingly, this patient was diagnosed with Leri-Weill dyschondrosteosis. Recently, many mutations have been reported in the SHOX gene. However, to date, mutation analysis of the SHOX gene for Leri-Weill dyschondrosteosis has not been reported in Korea as yet. We report the first case of a Leri-Weill dyschondrosteosis patient confirmed by mutation analysis of the SHOX gene.